Effect of segment structures on the hydrolytic degradation behaviors of totally degradable poly(L‐lactic acid)‐based copolymers. Issue 33 (29th April 2019) - Fan, Tiantang; Ye, Wuyou; Du, Beibei; Zhang, Qin; Gong, Li; Li, Jiafeng; Lin, Shengli; Fan, Zhongyong; Liu, Qing
ABSTRACT: A series of high‐molecular‐weight terpolymers named PTG‐ b ‐LG and PT‐ b ‐LG were synthesized based on the macroinitiators of PTG copolymers and PTMC, respectively. In vitro degradation of PTG‐ b ‐LG and PT‐ b ‐LG was carried out by immersing into PBS, in comparison with that of P L LA. Mass loss, water uptake, GPC, DSC, WAXD, and 1 H NMR were examined for the degradation study. It was found that PTG‐ b ‐LG degraded faster than PT‐ b ‐LG and P L LA due to the Di ‐random block structure, which had lower regularity of chain and lower crystallinity. The compositional changes appeared to be more complex, but the molar mass decreased owing to chain fragmentation caused by hydrolysis. Moreover, morphological changes were also observed during the degradation in all situations with the crystallization of by‐products and a preferential degradation of amorphous domains. Specifically, PTG‐ b ‐LG presented an adjustable degradation rate and may be used for the fabrication of totally biodegradation stents in the future. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47887. Abstract :